2021
DOI: 10.1088/1757-899x/1115/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ionosphere disturbance caused by the Lokon Volcano Eruption using GPS TEC data

Abstract: Eruption of Mount Lokon has the potential to cause danger to the community. The study of the ionospheric disturbances triggered by Lokon activity is very important to determine eruptive behavior. TEC anomaly before eruption is succesfully detected using correlation methods. Based on GPS TEC data from the GNSS satellite it was concluded that the TEC anomaly occurred three days before the eruption on July 14th, 2011. Using leveling method and polynomial technique, eruption effects on ionosphere were be determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…(2017) discovered that Sabancaya contained an exceptionally high relative water vapor abundance 6 months prior to its November 2016 eruption. In addition, abnormal changes in the total electron content (TEC) may also be caused by explosion‐triggered ionospheric perturbations during eruptions (Dautermann et al., 2009; Pandara et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017) discovered that Sabancaya contained an exceptionally high relative water vapor abundance 6 months prior to its November 2016 eruption. In addition, abnormal changes in the total electron content (TEC) may also be caused by explosion‐triggered ionospheric perturbations during eruptions (Dautermann et al., 2009; Pandara et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kern et al (2017 discovered that Sabancaya contained an exceptionally high relative water vapor abundance 6 months prior to its November 2016 eruption. In addition, abnormal changes in the total electron content (TEC) may also be caused by explosion-triggered ionospheric perturbations during eruptions (Dautermann et al, 2009;Pandara et al, 2021).The eruption of the Tonga volcano (TVE), located on an isolated island (20.546°S, 175.390°W) about 65 km north of Nuku 'alofa, the capital of Tonga in the South Pacific, occurred around 04:20 UTC on 15 January 2022. The eruption had a Volcano Explosive Index of 5 on a scale of 8, and can be considered a one-in-a-thousand-year eruption, severely affecting the related geophysical parameters.…”
mentioning
confidence: 99%
“…As for the specific direction of volcano‐ionosphere coupling research, it has been established that there is a correlation between ionospheric and volcanic activity, with TEC variation as an effective diagnostic parameter (Aoyama et al., 2016; Cahyadi et al., 2021, 2020; Heki & Fujimoto, 2022; Li et al., 2016; J.‐W. Lin, 2017; X. Liu et al., 2017; Maletckii & Astafyeva, 2022; Manta et al., 2021; Pandara et al., 2021; Saito, 2022; Shults et al., 2016; I. Toman et al., 2021; Verhulst et al., 2022; S.‐R. Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the study of anomalous propagation characteristics in the ionosphere, a variety of information can be obtained, including the location of volcanic source, the scale of volcanic eruption, the height of plume, the rate of material ejection and the quality of ejection materials (Cahyadi et al., 2020; Li et al., 2016; Maletckii & Astafyeva, 2022; Shults et al., 2016; Watson et al., 2022). In the study of volcanic eruption activity cycles, it has been found that ionospheric anomalies can occur several days before the main eruption event (Li et al., 2016; Pandara et al., 2021; I. Toman et al., 2021). Particularly, the enhancement of TEC has been observed to occur during the main phase of volcanic eruption (I. Toman et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation